LET's CONNECT Community Mentorship Program for Adolescents with Peer Social Problems: A Randomized Intervention Trial. - King, Cheryl A.; Gipson, Polly Y.; Arango, Alejandra; Lernihan, Deanna; Clark, Michael; Ewell Foster, Cynthia; Caldwell, Cleopatra; Ghaziuddin, Neera; Stone, Deborah (American Journal of Community Psychology, 2021)
This study examined the effectiveness of LET's CONNECT (LC), a community mentorship program based on the positive youth development model. Participants were 218 youth (66.5% girls), ages 12 to 15, who reported peer victimization, bullying perpetration, and/or low social connectedness. These youth were randomized to LC or the control group (community resource information). The LC program linked youth to community mentors who connected with youth and facilitated their involvement in social growth activities across a 16‐month period. Outcomes were assessed at 6 and 16 months with self‐report measures of social and community connectedness, thwarted belongingness, depression, self‐esteem, and suicidal ideation and behavior. In intent‐to‐treat analyses, LC was associated with modest positive effects for social connectedness, self‐esteem, and depression. It had no effects on suicidal ideation or behavior. Results suggest that LC has the potential to positively impact the developmental trajectories of youth dealing with the interpersonal challenges of victimization, bullying perpetration, or low social connectedness. LC implementation challenges and directions for further research are also discussed. Highlights: LET's CONNECT (LC) is a community mentorship program for youth with peer social problems.We examined the effectiveness of LC in a randomized intervention trial.LC was associated with modest benefits, including improved social connectedness and self‐esteem.LC may positively impact the developmental trajectories of youth with peer social problems.